A Narrative Review of Nicotine and Alcohol Addiction Recovery Content on TikTok - McCurdy, Li Yan; Potenza, Marc N. (Journal of the Korean Academy of Child and Adolescent Psychiatry, 2025)
Adolescent substance use remains a public health concern, and social media platforms may serve as potential intervention targets. The objective of this review is to characterize studies on anti-substance use and/or pro-recovery content on the TikTok social media platform. PubMed, Scopus, and Web of Science were searched for articles using search strings related to TikTok and substance use. Studies that characterized substance use content on TikTok and provided information on the associated hashtags were included. Studies that did not include hashtags reflecting anti-substance use or pro-recovery sentiments were excluded. Seven studies included hashtags that expressed being against, quitting, and/or recovering from substance use. Most previous studies focused on nicotine use. The content was largely created by adults. General content themes included motivations for reducing substance use, barriers to, and advice on how to reduce substance use, and personal recovery journey stories that celebrated success and normalized the recurrence of use. Some studies found that content created by individuals with lived experience and content focused on the benefits of quitting (rather than the costs of using) received higher engagement. Most studies noted that videos identified using anti-substance use hashtags often contain irrelevant or antithetical content. This review highlights the value of social media sites such as TikTok as potential platforms for encouraging reductions in substance use. Future studies should quantify whether viewing and engaging with such content leads to changes in real-world measures such as reduced consumption.